Transforming Informal Public Spaces into Formal Favorite Public Places for the Youth in Hanoi City in Consideration of Transgressive Activities with Critical Mapping and Participatory Spatial Visualization Approaches - Ta, Quynh Hoa; Nguyen, Quang Minh; Doan, The Trung; Phan, Tien Hau; Chu, Ngoc Huyen; Bui, Phuong Ngoc (International Journal of Sustainable Construction Engineering and Technology, 2024)
High-quality public space forms an indispensable part in the social life of any city worldwide. making the city vibrant and livable for all people. Attractiveness includes openness, accessibility, quality of landscape and spatial design, equipment, diversity of activities and so on. For the youth, transgressive activities are often the top factor of attractiveness today and represent a bold step in spatial design for use, because transgression is normally associated with the youth. However, as a new theme transgression has not been properly investigated in Vietnam. Thus, the authors aim to analyze those activities from different perspectives and identify which ones can be regarded as positive in order to be accepted, so that they can be allowed to take place in public places, hereby making them more attractive, at least to the youth as the majority of users. The research paper also explores what kinds of transgressive activities can be suitable to a particular public place through three case studies in Hanoi (one café, one footbridge and one alley), supported with mapping and participatory visualization as key research methods, and discusses how such a public place can be improved as a result of having something new to offer the youth. The initial research findings are expected to pave the way for future projects to study transgression in urban/peri-urban public places more systematically and comprehensively, first in theory and then in practice, in order to enhance the quality of those places as well as to “upgrade” them from “informal” to “formal” in terms of social awareness and legal recognition.